PENGELOLAAN KONTEN MEDIA SOSIAL INSTAGRAM SEBAGAI STRATEGI DIGITAL MARKETING HOTEL DAFAM EXPRESS JAKSA JAKARTA - Anisa Diniati; Muhammad Fahreza Al Ghifari; Sri Dewi Setiawati; Moch. Armien Syifaa Sutarjo (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
Social media content has an important role in building relationships between institutions and their consumers. In the process of managing social media content, each institution has a specific target audience and objectives to determine the message to be conveyed. This study aims to find out how the management of Instagram social media content is used by Hotel Hotel Dafam Express Jaksa Jakarta as a Digital Marketing Strategy. digital marketing built to gain public trust. The method used is to use a qualitative approach with a descriptive research type. The results of the study show that the efforts to manage digital media content by DEJJ can be said to be quite active, even though the response from the audience is still lacking or not many have responded. The content uploaded is quite diverse, ranging from promo content, information on health protocols implemented in hotels, tutorials on using self-check-in machines, to commemorations of religious and national holidays. Instagram social media is also used by DEJJ to interact with the audience. Keywords: content management, digital marketing, Instagram, social media